Defining the Pen Islands Caribou Herd of southern Hudson Bay - Kenneth F. Abraham; John E. Thompson (Rangifer, 1998)
In this paper, we describe the Pen Islands Herd of caribou, the largest aggregation of caribou in Ontario (it also occupies a portion of northeastern Manitoba). Photographic counts showed the herd had a minimum population of 2300 in 1979, 4660 in 1986, 7424 in 1987 and 10 798 in 1994. Throughout the 1980s, the Pen Islands caribou exhibited population behaviour similar to migratory barren-ground caribou herds, although morphology suggests they are woodland caribou or possibly a mixture of subspecies. The herd had well-defined traditional tundra calving grounds, formed nursery groups and large mobile post-calving aggregations, and migrated over 400 km between tundra summer habitats and boreal forest winter habitats. Its migration took it into three Canadian jurisdictions (Ontario, Manitoba, Northwest Territories) and it was important to residents of both Manitoba and Ontario. It is clear that the herd should be managed as a migratory herd and the critical importance of both the coastal and variable large winter ranges should be noted in ensuring the herd's habitat needs are secure.